2022
DOI: 10.3390/polym14153092
|View full text |Cite
|
Sign up to set email alerts
|

The Properties, Modification, and Application of Banana Starch

Abstract: Banana is a tropical fruit crop that is consumed at large, not only because of the quantity produced but also because it serves the calorific needs of millions of people. Banana is a potential source of high starch content (more than 60%). The application of starch for various purposes is dependent upon its structural, physicochemical, and functional properties. A native starch does not possess all required properties for specific use in the food product. To improve its application, starch can be modified phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 123 publications
4
15
0
3
Order By: Relevance
“…Therefore, due to their perishable nature, bananas must undergo additional processing to create other goods, such as banana flour. The advantages of processing bananas into banana flour include lengthening the period of storage, using them as adaptable raw materials, enhancing distribution security, and making them a useful material for processing [4]. As in our previous study, the unripe old banana fruit demonstrated higher anti-shigellosis activity than the ripe ones and it is more easier to make it into banana flour.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, due to their perishable nature, bananas must undergo additional processing to create other goods, such as banana flour. The advantages of processing bananas into banana flour include lengthening the period of storage, using them as adaptable raw materials, enhancing distribution security, and making them a useful material for processing [4]. As in our previous study, the unripe old banana fruit demonstrated higher anti-shigellosis activity than the ripe ones and it is more easier to make it into banana flour.…”
Section: Introductionsupporting
confidence: 58%
“…Banana flour is produced primarily for the following reasons: it is more durable in storage, can be utilized as a flexible raw material, increases distribution process safety, and is a useful material for processing [4]. Making it into banana flour also has the advantage of obtaining additional nutrients, including starch (84%), protein (6.8%), fat (0.3%), ash (0.5%), and food fiber (7.6%) [5].…”
Section: Discussionmentioning
confidence: 99%
“…fruit is recorded as one of the most economically important food sources and it is ranked as the fourth most cultivated crop, following rice, wheat, and maize in a worldwide level [ 1 , 2 ]. Banana is characterized as a low-cost food, providing high levels of energy because of its high composition in starch [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Como se observa en la tabla 1 el porcentaje de amilosa está cercano al 30,2 %, parámetro dentro de los porcentajes presentados en otras musáceas. (Marta et al, 2022). Es de anotar que el contenido de amilosa depende del origen botánico al que pertenece.…”
Section: Discussionunclassified
“…El plátano es un fruto del género Musa, el cual consiste en plantas herbáceas de origen asiático. (Marta et al, 2022) En Colombia se ha caracterizado por ser una actividad tradicional de la economía campesina y puede ser una alternativa para el aislamiento de almidón y posterior uso en la industria. (Moreno et al, 2021) El almidón es considerado como un polímero natural, con la capacidad de ser renovable y además biodegradable.…”
Section: Introductionunclassified